2015
DOI: 10.1080/10401334.2015.1077125
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Facing Medical Residents' Satisfaction in the Middle East: A Report From United Arab Emirates

Abstract: Respondents showed a substantial level of satisfaction with the residency training. The vast majority of residents (80%, N = 88) believe that their residency program curriculum and rotation was "good," "very good," or "excellent." Areas of dissatisfaction included salary, excessive paperwork during rotations, and harassment. INSIGHTS: This is the first report that studies the satisfaction of medical residents in all specialties in Dubai, UAE. Our findings provide preliminary evidence on the efficiency of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…[ 28 29 ] The country has two main medical residency training programs, one in Abu Dhabi and the other in Dubai; both being accredited by Arab Board of Health Specializations. [ 30 31 32 ] Several factors related to career choices among medical students,[ 28 29 33 ] accreditation perception among residents and resident’ satisfaction of the residency program in Dubai and Abu Dhabi were recently addressed. [ 30 34 ] In spite, a concerted nationwide study to understand and address burnout and depression in the medical residency program has not been conducted not only in the UAE but also the region in general.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 28 29 ] The country has two main medical residency training programs, one in Abu Dhabi and the other in Dubai; both being accredited by Arab Board of Health Specializations. [ 30 31 32 ] Several factors related to career choices among medical students,[ 28 29 33 ] accreditation perception among residents and resident’ satisfaction of the residency program in Dubai and Abu Dhabi were recently addressed. [ 30 34 ] In spite, a concerted nationwide study to understand and address burnout and depression in the medical residency program has not been conducted not only in the UAE but also the region in general.…”
Section: Introductionmentioning
confidence: 99%
“…[ 30 31 32 ] Several factors related to career choices among medical students,[ 28 29 33 ] accreditation perception among residents and resident’ satisfaction of the residency program in Dubai and Abu Dhabi were recently addressed. [ 30 34 ] In spite, a concerted nationwide study to understand and address burnout and depression in the medical residency program has not been conducted not only in the UAE but also the region in general. To address this gap, a nationwide, multicenter, cross-sectional study was designed to evaluate professional burnout and depression among medical residents in the UAE.…”
Section: Introductionmentioning
confidence: 99%
“…A multiregional study involving medical practitioners from UK, Europe, North America, and Asia suggested that the variation in aspects of professionalism might be due to diverse cultural and socio-economic backgrounds. [5]…”
Section: Introductionmentioning
confidence: 99%
“…High-risk cases, such as multiple CS and multiparity are commonly handled by the Dubai Health Authority (DHA), a public sector healthcare provider in Dubai with four hospitals and 16 primary health care centers. Dubai public hospitals, governed by the DHA are accredited by the Joint Commission International and serve as teaching hospitals for medical students and residency training ( 12 , 13 ) . A vast majority of the physicians in the DHA network are either trained in the United States or Europe.…”
Section: Introductionmentioning
confidence: 99%